VasoTracker, a Low-Cost and Open Source Pressure Myograph System for Vascular Physiology - Lawton, Penelope F.; Lee, Matthew D.; Saunter, Christopher D.; Girkin, John M.; McCarron, John G.; Wilson, Calum (Frontiers in Physiology, 2019)
Pressure myography, one of the most commonly used techniques in vascular research, measures the diameter of isolated, pressurized arteries to assess the functional activity of smooth muscle and endothelial cells. Despite the widespread adoption of this technique for assessing vascular function, there are only a small number of commercial systems and these are expensive. Here, we introduce a complete, open source pressure myograph system and analysis software, VasoTracker, that can be set-up for approximately 10% of the cost of commercial alternatives. We report on the development of VasoTracker and demonstrate its ability to assess various components of vascular reactivity. A unique feature of the VasoTracker platform is the publicly accessible website (http://www.vasotracker.com/) that documents how to assemble and use this affordable, adaptable, and expandable pressure myograph.